Prinsip Non-Intervensi di Era Krisis Kemanusiaan: Reinterpretasi Normatif dalam Tindakan Perserikatan Bangsa-Bangsa - Edward Benedictus Roring; Thalia Salma Putri Kamilah; Akmal Zaki; Faiz Aryaputra; Livia Haris; Salman Alfarisi; Diani Sadiawati (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
The principle of non-intervention is the main foundation in international relations that affirms the prohibition of interference by other countries in the domestic affairs of a country. However, increasingly complex global dynamics, especially related to the increasing humanitarian crises such as genocide, ethnic cleansing, and systematic human rights violations have raised serious challenges to the absolutism of the principle. This article aims to analyze how the principle of non-intervention is normatively reinterpreted in the practices and actions of the United Nations (UN), especially through the Responsibility to Protect (R2P) doctrine. Using a juridical-normative approach and case studies of interventions in Rwanda, Kosovo, and Syria, this study reveals a shift in the meaning of non-intervention from an absolute prohibition to a limited allowance for humanitarian protection. This finding confirms that in conditions of extreme humanitarian crises, the legitimacy of international action is not only measured by state sovereignty, but also by the moral and international legal obligations to protect civilians. The UN, as a multilateral actor, plays a key role in balancing the principle of non-intervention with humanitarian imperatives, thus giving rise to dynamic and contextual normative reinterpretations.